Classification of Students' Non-Routine Problem Solving Skills. (July 2020) - Sita Pramayudi, A A A; Sudiarta, IGP; Astawa, IWP
Abstract: Non-routine mathematical problems are complex problems that require a level of creativity and uniqueness in solving them. Classification students' characteristics of solving non-routine problems have not been many researchers who provide an overview. This study aims to classify the characteristics of students' problem solving skills. This type of research is a qualitative study involving five students of class VIII at SMP Negeri 1 Kintamani. Five students were selected through a purposive sampling technique on the condition that students of class VIII have high, medium and low mathematical skills. Data regarding non-routine mathematical problem solving students are collected through problem solving tests and supported by interview tests to obtain a picture of students' ability to understand the questions along with an understanding of the answers that have been done. Data were analyzed with data reduction, data presentation, and data verification steps. Data that has been verified are analyzed using the constant comparison method. Characteristics of non-routine mathematical problem solving students can be classified into 4 levels, namely Level 1 (students' understanding of problems along with mathematical problem solving is very lacking), Level 2 (Students' understanding of problems less and students' problem solving is lacking but able to plan problem solving), Level 3 (students 'understanding of problems takes a long time and students' problem solving is good), and Level 4 (students 'understanding of problems is good and students' problem solving is very good). Classification is obtained based on reference to problem solving according to Polya.